Analyzing the Regional Economic Underpinnings of Foreign Direct Investment Sustainability in East Kalimantan Post-Ibu Kota Nusantara Relocation - , Yogi Adi Riyanto; , Sri Suharsih; , Hariestya Zaki Akmal Aulia; , Ilyasin Aditya Rahman (Archives of Current Research International, 2025)
The development of Indonesia’s new capital city named Ibu Kota Nusantara (IKN) in East Kalimantan Province, which commenced in 2022, was expected to attract increased Foreign Direct Investment (FDI) in this region. However, the significant surge in investment during 2022 appears to have been only an initial stimulus. Therefore, this study aims to examine other determinants that may explain the fluctuations in FDI in East Kalimantan. This study analyzes district-level determinants of FDI in East Kalimantan using localized indicators, addressing research gaps and capturing spatial-economic dynamics in the post-IKN development phase of a resource-based regional economy. Using panel data from 10 East Kalimantan districts and cities during 2019–2024, this study employs a quantitative methodology. The independent variables tested include Oil Palm Land Area (OPLA), Implicit Index of Gross Regional Domestic Product (IIGRDP), Domestic Direct Investment (DDI), and Palm Oil Production (POP). The Badan Pusat Statistik (BPS) provided the data. Panel data regression utilizing the Ordinary Least Squares (OLS) approach is used in the study methodology. The Random Effects Model (REM) is the best model after model specification testing using the Chow, Hausman, and Lagrange Multiplier tests. The estimation results show that the four independent variables have a significant positive relationship with FDI. An R-squared value of 0.6259 suggests that the model has a relatively strong ability to explain the variation in FDI. These findings underscore the pivotal role of synergizing the productivity of leading sectors, maintaining price stability, and fostering dynamic domestic investment in shaping a conducive and attractive investment climate. This study recommends the establishment of an Artificial Intelligence-based Green Investment Command Center (GICC) to map sustainable investment zones and transparency with ESG (Environmental, Social, Governance) standards. These policy implications are relevant for commodity-producing regions in developing countries, though limited by the study’s timeframe and regional economic focus.